Agriculture-Industry terms of trade (United nations, 1979)
This studies have show that niter-sectoral terms of trade are, in fact, carriers and reflectors of the stregths and weaknesses of the agriculture-industry linkages and that it is possible to influence the quality and durability of these linkages through appropriate policy interventions and institutional arrangements.